Performance Analysis of Hybrid Amplifiers in Optical Communication Systems - Kumar, Sanjiv (My University, 2012)
The demand for high capacity long-houl telecommunication system increasing at a study rate, So that to satisfy the requirement on long distances, the communication channel must have a very low cost. Optical fiber is the only transmission medium offering such longer bandwidth with low loss communication links. Fiber optics has made a revolutionary change in telecommunication over the past few decades. The electronic regeneration has become expensive and also limited transmission rate, so that a means of optical amplifier was sought. Which increase transmission rate and eliminated the costly conversions from optical to electrical signals and vice–versa. Optical amplifiers amplify signals at different wavelength simultaneously. Basically here we discuss two types of Optical Amplifiers i.e. Semiconductor optical amplifiers and Fiber amplifiers and further classified into traveling wave semiconductor optical amplifier, fabry-perot semiconductor optical amplifier, Erbium doped fiber amplifier, Raman & Brillouin fiber amplifiers. Optical amplifiers are the fundamental building blocks required for the development of future all optical networks. The amplifiers are based on semiconductor laser structures or doped optical fibre and in recent years there has been rapid and dramatic progress in their development. Currently fibre optical amplifiers are at a stage where they could be deployed in real networks. In this thesis, I used 64 channel WDM systems at 10 Gbps and I have been investigated for the various optical amplifiers and hybrid amplifiers and the performance has been compared on the basis of transmission distance, presence and absence of nonlinearities and pumping. The amplifiers EDFA , RAMAN and SOA have been investigated independently and further compared with hybrid amplifiers like EDFA-EDFA, RAMAN-EDFA, RAMAN-SOA EDFASOA, EDFA-RAMAN, RAMAN-EDFA-SOA and SOA-RAMAN-EDFA. It is observed that optical hybrid amplifier RAMAN-SOA and SOA-RAMAN-EDFA provides the highest output gain (24.56 dB and 27.31 dB) ,least bit error rate (1 × 10 -40 and 1 × 10 ) and good eye diagram at 160 km for presence and absence of nonlinearities as compare to other optical amplifier as compare to other optical amplifier. Four types of pumping have been investigated independently and compared. It is observed that pump 3 of RAMAN-EDFA -40 iii provides the highest output power (10.64 dBm and 10.69 dBm ) and least bit error rate (1 × 10 -40 and 1 × 10 -40 ) at 160 km for presence and absence of nonlinearities respectively as compare to other pumping amplifier.
Keywords: EDFA,SOA, RAMAN, HYBRID AMPLIFIERS